Effect of heat treatment on hardness and wear properties of an aluminum alloy of motorcycle piston - Mohd Fizam Hj Zainon (School of Mechatronics Engineering, Universiti Malaysia Perlis, 2010)
The present study was undertaken to investigate the effect of heat treatment on the microstructure, hardness and wear of aluminum alloys piston and with the aim to improve the mechanical properties by using heat treatment method.